The Influence of Pre-Trip Medical Spanish Education on a US-Based, Medical Student Service Trip: A Cohort Study - Evensen-Martinez, Maison; Santiago, Mariangela; Martinez, Roger; Beck, Dallin; Trawick, Ann; Zapata, Isain; Wardle, Mark (International Journal of Medical Students, 2024)
Background: International service trips are increasingly common in medical school curricula. Medical Spanish is an essential tool in healthcare interactions with Spanish-speaking patients globally. Medical Spanish classes are offered at many medical schools, but it is not known whether they increase confidence for medical students on Spanish-speaking service trips. Methods: A prospective cohort study of medical students attending one of two sister campuses who completed pre- and post-international medical service trip questionnaires. Data collected includes demographics, confidence, and perceived experiences. Data analyses involved a multivariable regression assuming an ordered multinomial response, FREQ procedure, and the GLIMMIX procedure on SAS STAT v.9.4. Results: Demographics significantly associated with confidence categories are female sex, length of Spanish education, previously having lived in a Spanish country, and experience speaking Spanish with patients. Confidence communicating in Spanish shows the highest gain in significant categories post-trip while confidence working with interpreters and feeling adequately trained to treat Hispanics showed the lowest. Participants having taken Medical Spanish before did not improve their confidence. However, participants with prior Medical Spanish experience reported significantly higher benefit from this education in that it gave them an advantage and helped them connect better with patients. Conclusion: Our findings reinforce the importance of language-concordance and confidence in patient interactions while demonstrating that prior Medical Spanish experience may not significantly improve confidence on a Spanish-speaking international trip, especially among non-fluent students. Spanish experience and proficiency should not be a deterring factor for students looking to go on a medical trip.